Temperature Correction for FWD Deflection in Cement Pavement Void Detection - Bei Zhang; Xiaoliang Wang; Yanhui Zhong; Xiaolong Li; Meimei Hao; Yuanhao Ding; Jianyang Liu; Xu Zhang (Advances in Civil Engineering)
The use of the falling weight deflectometer (FWD) for detecting pavement voids is based on the principle that, under the same impact load, the deflection of pavements with voids increases significantly. Under the effect of temperature, the cement pavement becomes warped, which affects the deflection detection accuracy. In order to improve the accuracy of FWD detection of cement pavement voids, a three-dimensional numerical model of cement pavement on a multilayered elastic foundation under the coupled action of temperature and load is established in this paper. In addition, under different pavement void, climatic, and load conditions, the influence of temperature difference between top and bottom of the plate on the deflection of the center point of plate angle load is studied. Considering the temperature difference between top and bottom, the temperature correction coefficient is established and experimentally verified the accuracy of the temperature correction coefficient. The results showed that, within the ranges of positive and negative temperature differences, the fitting degree of the temperature correction coefficient for the cement pavement exceeded 0.99, which was consistent with the variation trend of the temperature correction coefficient obtained through field tests. The error was lower than 7%, which verified the applicability of the temperature correction coefficient for the dynamic deflection of cement pavements based on FWD. The accuracy of the FWD method in detecting cement pavement voids was improved, and this study demonstrated theoretical reference value and practical engineering significance.